Low velocity impact analysis on glass fiber reinforced composites with varied volume fractions. Issue 1 (17th February 2015) - Reghunath, Rakesh; Lakshmanan, Mahadevan; Mini, K M
Abstract: This paper presents an experimental study to assess the impact response of bidirectional woven type of glass fiber reinforced composite material with varied volume fractions and hence to find out the optimal volume fraction which gives better impact resistance. The specimens are prepared using vacuum bagging process and the volume fraction is estimated by resin burn off method. For getting information regarding surface topography of the impacted specimen, scanning electron microscopy is conducted. The study is done by slightly varying the velocities and it is found that a volume fraction of 43 -44% gives a better impact resistance which is also confirmed by the scanning electron microscopy test. From the SEM results it is observed that matrix cracking, fiber breakage, debonding and fiber pull out are the major modes of failure during the impact, which reduces the structural strength and stability of the structure.